Development And Application Of Expressed Sequence Tags And Dna Microarray For Somatic Embryogenesis In Oil Palm - Low, Leslie Eng Ti (2009)

(untitled)
Oil palm (Elaeis guineensis Jacq.) is one of the most important oil bearing crops in the world. However, genetic improvement of oil palm through conventional breeding is extremely slow and costly, as the breeding cycle can take up to 10 years. This has brought about interest in vegetative propagation of oil palm. Since the introduction of oil palm tissue culture in the 1970s, clonal propagation has proven to be useful in producing uniform planting materials. However, despite considerable progress in improving the tissue culture techniques, the callusing and embryogenesis rates from proliferating callus cultures remain very low. Thus, understanding the gene diversity and expression profiles during somatic embryogenesis is critical in increasing the efficiency of these processes. To achieve this, a total of six standard cDNA libraries, representing three developmental stages (nonembryogenic callus, embryogenic callus and embryoids) in oil palm tissue culture, were generated in this study. Random sequencing of clones from the embryogenic callus cDNA libraries generated 2,716 expressed sequence tags (ESTs). These ESTs were combined with 14,883 ESTs available in MPOB’s EST programme. The 17,599 ESTs were analysed, annotated and assembled to generate 9,584 putative unigenes distributed in 3,268 consensi and 6,316 singletons. These unigenes were assigned putative functions based on similarity and gene ontology annotations. A subset of these ESTs were selected and spotted on cDNA microarrays. Both the EST and microarray data analysis were able to identify expression profiles that could differentiate non-embryogenic callus from embryogenic samples. The in silico EST data analysis identified 52 unigenes that showed potential to be developed as candidate markers for embryogenesis. The microarray experiment identified 76 unigenes that could differentiate non-embryogenic callus from embryogenic callus, embryoids and shoots from polyembyoids. The EST and microarray data analysis revealed that lipid transfer proteins were highly expressed in embryogenic tissues. The results also showed that glutathione S-transferases were highly expressed in non-embryogenic callus. This study has provided an overview of genes expressed during oil palm tissue culture and real-time PCR analysis identified four genes (pOP-EA00703, pOP-EA01249, pOP-EA01117, pOP-SFB01045) that had the potential to be developed as molecular markers for embryogenesis.